Space charge distribution and leakage current pulses for contaminated glass insulator strings in power transmission lines - Othman, Nordiana Azlin (The Institution of Engineering and Technology, 2017)
This study reports an investigation on space charge distribution and leakage current (LC) pulses of four units of glass insulators recently removed from service. Simulation works were conducted using finite element software and validated by laboratory experiments. The simulation and experimental results were found to be in good agreement when studying the space charge distribution pattern along the glass insulator string. It is evident that the LC waveform can be used to characterise the types of partial discharge according to their occurrence with respect to the AC supply. Thus, the proposed method is viable and reliable to be applied in an online measurement system.